ChemInform Abstract: Direct (Het)Arylation of Fluorinated Benzothiadiazoles and Benzotriazole with (Het)Aryl Iodides. Issue 31 (5th August 2014) - He, Chun‐Yang; Wu, Cai‐Zhi; Qing, Feng‐Ling; Zhang, Xingang
Abstract A simple and efficient method to prepare a wide range of symmetrical and unsymmetrical fluorinated benzothiadiazole—arene molecules as well as benzotriazole analogues is reported.